2006
DOI: 10.1160/th05-12-0782
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 potentiates LPS-induced neutrophil activation through a JNK–mediated pathway

Abstract: Plasminogen activator inhibitor-1 (PAI-1), a member of the serine protease inhibitor superfamily, modulates fibrinolysis by interacting with proteolytic mediators, including urokinase plasminogen activator (uPA). Although the roles of uPA and PAI-1 in plasmin generation and the degradation of fibrin are well known, recent evidence also suggests that they can participate in acute inflammatory conditions that involve neutrophil activation. In the present experiments, we found that the addition of PAI-1 to LPS- s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 20 publications
4
33
0
Order By: Relevance
“…Because apoptotic cell clearance is critical to the resolution of inflammation, our data suggest that PAI-1 may exacerbate inflammatory responses by blocking the clearance of apoptotic neutrophils, thereby allowing such neutrophils to become necrotic and to release their intracellular contents into the extracellular milieu. Our findings, together with previous studies demonstrating that PAI-1 enhances LPS induced neutrophil activation (22) and promotes the migration and infiltration of lymphocytes and neutrophils into inflammatory sites (19)(20)(21)27), demonstrate that PAI-1 has multiple proinflammatory roles that are independent of its participation in coagulation and microvascular thrombosis. We found that the enhanced neutrophil phagocytosis associated with PAI-1 deficiency can be abrogated by blocking LRP on macrophages with anti-LRP antibodies or the LRP-specific blocking peptide RAP, indicating that LRP participates in PAI-1 mediated modulation of efferocytosis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Because apoptotic cell clearance is critical to the resolution of inflammation, our data suggest that PAI-1 may exacerbate inflammatory responses by blocking the clearance of apoptotic neutrophils, thereby allowing such neutrophils to become necrotic and to release their intracellular contents into the extracellular milieu. Our findings, together with previous studies demonstrating that PAI-1 enhances LPS induced neutrophil activation (22) and promotes the migration and infiltration of lymphocytes and neutrophils into inflammatory sites (19)(20)(21)27), demonstrate that PAI-1 has multiple proinflammatory roles that are independent of its participation in coagulation and microvascular thrombosis. We found that the enhanced neutrophil phagocytosis associated with PAI-1 deficiency can be abrogated by blocking LRP on macrophages with anti-LRP antibodies or the LRP-specific blocking peptide RAP, indicating that LRP participates in PAI-1 mediated modulation of efferocytosis.…”
Section: Discussionsupporting
confidence: 80%
“…Isolation of bone marrow neutrophils was as described (22,29). Peritoneal macrophages were isolated 5 days after i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased pulmonary levels of urokinase plasminogen activator (uPA) and plasminogen activator inhibitor 1 (PAI-1) are present in ALI, and both uPA and PAI-1 are able to potentiate neutrophil activation (6 -10). Interaction of PAI-1 with the serine protease domain of uPA results in inhibition of the fibrinolytic, but not the proinflammatory activity of uPA, and appears to contribute to the development of microvascular thrombi and alveoli fibrin deposition that are characteristic histologic findings in ALI (6,7,10). Increased bronchoalveolar lavage levels of PAI-1 are associated with worse clinical outcome from ALI (11).…”
Section: A Cute Lung Injury (Ali)mentioning
confidence: 98%
“…These results may be attributed to the ascribed function of PAI-1 in regulating fibrinolysis or a potential role of PAI-1 in mediating neutrophil recruitment signals, as was demonstrated in vitro. 55 In either case, these results suggest that PAI-1 function may prove to be a useful alternative target in the battle against bacterial pathogens.…”
Section: -22mentioning
confidence: 96%